العلاقة بين الهطل المطري ومناسيب المياه الجوفية في السهل الساحلي لنهر الكبير الشمالي - سورية - الأسعد, علي محمد; حايك, شريف بدر; عمّار, غطفان عبد الكريم; عبد الرحمن, عباس (Latakia University Journal -Engineering Sciences Series, 2014)
تشهد منطقة الحوز الأدنى لنهر الكبير الشمالي نشاطاً اقتصادياً مهمّاً، تزداد معه الحاجة إلى المياه. وتهدف الدراسة إلى تحديد العلاقة بين كمية الهطل وتغيّر مناسيب المياه الجوفية. تنتشر في المرتفعات صخور كلسية ومارلية مشققة ذات نفوذية عالية، بينما تنتشر توضعات متوسطة إلى قليلة النفوذية في السهول الساحلية، وتتوضّع المياه الجوفية على عمق قليل من سطح الأرض، وتستجيب مناسيبها بسرعة كبيرة نسبياً لتسرب مياه المطر ومياه الري ما يجعل تلوّثها وتأثّرَها بالعوامل الجوية سهلاً وسريعاً، وستتأثر بالتغيرات المناخية بسهولة. وتبيّن نتيجة معالجة البيانات الحقلية ومناقشتها أنّ تغيّرات مناسيب المياه الجوفية ترتبط بعوامل طبيعية واصطناعية متعددة ومتداخلة التأثير في مناسيب المياه الجوفية، فبعضُها يزيد تغذيةَ المياه الجوفية وارتفاع مناسيبها، وبعضها الآخر له تأثير معاكس، بحيث لا يمكن وضع علاقة رياضية بين مناسيب المياه الجوفية وكميات الهطل المطري، بسبب التأثير المتزامن لهذه العوامل، التي يصعب عزلها ومراقبتها في وضعها الطبيعي. Al-Kabeer River Coastal Plain faces very important economic activities which lead to growing water demands. This research aims to define the relationship between rainfall and subterranean-water levels. In the mountainous area fissured marl and limestone with high permeability spread. However, on the coastal plateau deposits with moderate to low permeability values spread, and water levels quickly respond to rainfall and irrigation water, which makes it get easily polluted and affected by climatic factors. Analyses and discussions of field data have led to the fact that subterranean-water levels are to do with many natural and artificial interrelated parameters. And in some cases, they can be adversely oriented, and difficult to isolate and monitor separately, and become very difficult to derive mathematical formula for describing the relationship between just two parameters (subterranean-water percentages and rainfall levels).